Preclinical evaluation of the neutralising efficacy of three antivenoms against the venoms of the recently taxonomically partitioned E. ocellatus and E. romani. - Rebecca J Edge; Amy E Marriott; Molly Keen; Tiffany Xie; Edouard P Crittenden; Charlotte A Dawson; Mark C Wilkinson; Wolfgang Wüster; Nicholas R Casewell; Stuart Ainsworth; Stefanie K Menzies (PLoS Neglected Tropical Diseases)
Snakebite is a significant public health concern in Africa, with the viperid species Echis ocellatus being responsible for the majority of snakebite deaths in West Africa. Recently E. ocellatus underwent taxonomic revision and was split into two species, E. ocellatus sensu stricto and E. romani, leading to questions regarding differences in venom bioactivities and the efficacy of antivenoms indicated for treatment of 'E. ocellatus' envenoming against the two redefined species. Using a range of in vitro assays we compared the toxin activities of the two species and the venom-neutralising efficacy of three antivenoms (EchiTAbG, SAIMR Echis and Echiven) raised against 'E. ocellatus'. We then used murine preclinical assays to compare the in vivo efficacy of these antivenoms against E. romani and E. ocellatus s. str venoms. Mitochondrial barcoding of snake skins and venom revealed that E. romani, and not E. ocellatus, is used in the manufacture of several antivenoms raised against 'E. ocellatus'. There were also a number of differences in specific toxin activity between the venoms of the two species in the three in vitro assays utilised in this study.; E. ocellatus (Ghana) had the strongest phospholipase A2 (PLA2) activity, followed by weak PLA2 activity for E. romani (Cameroon) and insignificant activity by E. romani (Nigeria). E. ocellatus (Ghana) and E. romani (Nigeria) demonstrated comparable snake venom metalloproteinase activity, whilst E. romani (Cameroon) had reduced, albeit still significant, activity in comparison. However no differences were observed in a plasma clotting assay measuring coagulopathy between the venoms and localities. Venoms from E. ocellatus (Ghana) and E. romani (Cameroon and Nigeria) were all recognised comparably by the three antivenoms, and there were only modest differences between antivenoms in neutralising the various in vitro toxin effects. In murine preclinical assays, each antivenom could neutralise the lethal effects of E. romani (Nigeria), but differences were seen in their comparative potency when the same antivenom doses were tested against E. romani (Cameroon) and E. ocellatus (Ghana). In these comparative potency assays, all three antivenoms were unable to confer 100% survival when tested against E. romani (Cameroon), but SAIMR Echis provided the best protection with 80% survival. When tested against E. ocellatus (Ghana), the comparative doses of SAIMR Echis and Echiven provided 100% protection whereas EchiTAbG failed to prevent lethality beyond three hours. This represents the first detailed analysis of differences between E. ocellatus and E. romani venom bioactivities and the efficacy of existing antivenoms against these two species. Our findings demonstrate that EchiTAbG, SAIMR Echis and Echiven antivenoms are preclinically efficacious against the lethal effects of E. ocellatus and E. romani venom across a number of localities.